"Guns Don't Kill People … Selfies Do": rethinking narcissism as exhibitionism in selfie-related deaths. Issue 3 (27th May 2017) - Maddox, Jessica
ABSTRACT: This work explores how the Narcissus myth has been inaccurately adopted by media, specifically in the reporting of selfie-related deaths. Narcissus, a boy in love with his own image, loved himself so much he would not share his image with others. Considering sharing is an integral part of the selfie phenomenon, this work seeks to dismantle the narcissism misuse in media coverage of selfie-related deaths. Through critical textual analysis of six major newspapers, I argue that exhibitionism is a more accurate critique of the selfie. Furthermore, it is a critique that fits more in line with the digital age, as opposed to the analog nature of narcissism.